STUDYING THE NATURE OF EXOTIC BLACK HOLES - M. Melibaev (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Considered theoretical model of creation Black Holes as solution Schwarzschild metric of Einstein’s equation. As considered as final achievements hunger and binary Black Holes Systems which accretion leading to perturbation of space-time metric structure and create gravitational waves.